2007
DOI: 10.14411/eje.2007.029
|View full text |Cite
|
Sign up to set email alerts
|

Comparative behavioral and EAG responses of female obliquebanded and redbanded leafroller moths (Lepidoptera: Tortricidae) to their sex pheromone components

Abstract: Abstract. Studies were conducted investigating the responses of female obliquebanded leafrollers, Choristoneura rosaceana (Harris) and redbanded leafrollers, Argyrotaenia velutinana (Walker) (Lepidoptera: Tortricidae), to components of their sex pheromone. Electroantennogram (EAG) recordings revealed significant responses from antennae of female moths of both species to the major pheromone component, (Z)-11-tetradecenyl acetate, at dosages ranging from 2 µg -2 mg. However, tested individually, the minor pherom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 60 publications
(60 reference statements)
0
11
0
Order By: Relevance
“…Moreover, based on the higher expression of MvitPBP1 gene in male M. vitrata than that of the other PBP genes, MvitPBP1 gene might have a major role in male-female recognition. Furthermore, female-biased expression of both of MvitPBP2 and MvitPBP3 genes might indicate involvement in the autodetection of sex pheromone compounds, which has been demonstrated in other lepidopterans 47 48 49 50 .…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, based on the higher expression of MvitPBP1 gene in male M. vitrata than that of the other PBP genes, MvitPBP1 gene might have a major role in male-female recognition. Furthermore, female-biased expression of both of MvitPBP2 and MvitPBP3 genes might indicate involvement in the autodetection of sex pheromone compounds, which has been demonstrated in other lepidopterans 47 48 49 50 .…”
Section: Discussionmentioning
confidence: 76%
“…Alternatively, PBPs expressed in female antenna may play a role in the autodetection of pheromone compounds. Autodetection has been demonstrated by electroantennography in some Lepidoptera species (Gokce et al, 2007;Groot et al, 2005;Stelinski et al, 2006;Yang et al, 2009). Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, the response of unmated males to pheromone blends has been well documented in earlier studies 24 . Autodetection was earlier reported from other moths such as Panaxia quadripunctaria 14 , Choristoneura rosaceana 25 and Grapholitha molesta (Busck) 26 . The role of sensilla trichodea in the perception of sex pheromones of females in H. armigera and other moths was reported by earlier workers 27,28 .…”
Section: Discussionmentioning
confidence: 60%
“…Exposure to pheromone-permeated ovipostional sites reduced egg laying in females of C. rosaceana and Aryrotaenia velutinana 25 . However, in the present study no change was observed in the oviposition behaviour of H. armigera.…”
Section: Discussionmentioning
confidence: 95%